KADAR HAEMOGLOBIN (HB) ANTARA AKSEPTOR KONTRASEPSI IUD NOVA-T DAN COOPER-T CU 380 A - Zakkiyatus Zainiyah (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2020)
IUD is an advice longterm contraception among others. Cooper-T and Nova-T are the most used by women in 20-35 years old. Bleeding is one of complication from using IUD especially Cooper-T and Nova-T. The bleeding decrease hemoglobin on blood circulation. The Purpose of this study to analyze levels haemoglobin between contraception acceptors Nova-T IUD and Cooper-T CU 380 A menstruation periode The research method is analytical research with cross sectional. The independent variable is IUD contraceptive acceptors. The dependent variable is the level of hemoglobin (Hb). Sampling technique used is simple random sampling. The population of the research are acceptors in the region IUD in Puskesmas Taman sidoarjo were 38 respondent. The Analysis of univariate data is the frequency distribution. The Bivariat analysis used chi square. This reseacrh the data analyze using T independent test.The results showed that the average haemoglobin levels at the acceptor IUD Cooper-type T is 10.4 gr/dl. While the acceptor IUD type of Nova-T the average haemoglobin levels was 11.8 gr/dl. Based on Chi square Test P value <α (0.003 < 0.05) so that Ha is accepted that means There is The Differences in hemoglobin between acceptors IUD Cooper-T Cu 380 A and Nova-TThe result show that the hemoglobin’s value of Cooper-T is lower than Nova-T. Based on teory, it caused there are somedifference of shape and volume of Cooper-T bigger than Nova-T and it has more coil that made a bigger and deeper wound causing heavy bleeding. Recommended for patients to use the Nova-T IUD.